Mechanical and Barrier Properties of PVP-Carbon Dot Nanocomposite Films - Ahmad Sjahriza; Zainal Alim Mas’ud; Komar Sutirah (Research Center for Chemistry - LIPI, 2018)
This research reported carbon dot were synthesized form citric acid and urea through a single step microwave process and Poly Vinyl Pirrolidone (PVP) films composited by carbon dot were prepared. The effects of different composition carbon dotsÂ on mechanical strength of films and water vapour barrier were evaluated. Highest mechanical yielded composite film were analyzed their thermal stability. Average of carbon dot diameter was found 90.61 nm and polydispersity indice 0.396. Different composition carbon dot exhibit significant improvement in tensile strength and modulus. Water permeablity of films varieate with content of carbon dot. The presence of carbon dot had a negligible effect on Tg of film and show melting process.